2018
DOI: 10.1038/s41388-018-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

LMTK3 confers chemo-resistance in breast cancer

Abstract: Lemur tyrosine kinase 3 (LMTK3) is an oncogenic kinase that is involved in different types of cancer (breast, lung, gastric, colorectal) and biological processes including proliferation, invasion, migration, chromatin remodeling as well as innate and acquired endocrine resistance. However, the role of LMTK3 in response to cytotoxic chemotherapy has not been investigated thus far. Using both 2D and 3D tissue culture models, we found that overexpression of LMTK3 decreased the sensitivity of breast cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…The results showed higher LMTK3 expression was correlated with progression and poor prognosis in breast cancer [22]. Interestingly, LMTK3 also enhanced resistance to endocrine therapy in breast cancer by reducing autophagy [23] and confers chemoresistance in breast cancer by the formation of cH2AX foci [9]. It has also been reported that LMTK3 was an oncogene and a significant prognostic marker in colorectal cancer, lung cancer, gastric cancer, gastrointestinal stromal tumor and melanoma [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed higher LMTK3 expression was correlated with progression and poor prognosis in breast cancer [22]. Interestingly, LMTK3 also enhanced resistance to endocrine therapy in breast cancer by reducing autophagy [23] and confers chemoresistance in breast cancer by the formation of cH2AX foci [9]. It has also been reported that LMTK3 was an oncogene and a significant prognostic marker in colorectal cancer, lung cancer, gastric cancer, gastrointestinal stromal tumor and melanoma [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenetic role of LMTK3 in breast cancer has been confirmed by several studies [6][7][8]. LMTK3 promotes breast cancer progression and decreased the sensitivity to doxorubicin treatment by decreased activity of ataxia-telangiectasia mutated kinase [9]. Shi et al [10] found that expression of preoperative soluble LMTK3 (sLMTK3) is an independent prognostic factor for patients with colorectal cancer compared with patients with low levels of sLMTK3, and patients with high sLMTK3 expression showed a poorer overall survival.…”
Section: It Can Catalyze Protein Phosphorylation and Directly Ormentioning
confidence: 93%
“…With comprehensive profiling of CAL-101 mediated changes in the secretome of fibroblast cell lines established, next we investigated how these secreted proteins altered the transcriptional state of MDA-MB-231 cells. We cultured MDA-MB-231 in a transwell along with CAL-101 or vehicle-treated MRC5 cells for 24 hours and total RNA was extracted from MDA-MB-231 and processed as described earlier (36). As anticipated, whole transcriptome data showed a high degree of similarity between replicate samples and most significant variations between MDA-MB-231 cells co-cultured with CAL-101 treated or untreated MRC5 cells (Supplementary Figure 11).…”
Section: Integrated Secretome and Transcriptomic Analyses Reveal Fibrmentioning
confidence: 67%
“…Cell viability assay was performed as previously described (69) (36). Briefly, cells were seeded in 5.000 for well in a 96 well plate and treated with the indicated compound and time points and cell viability was evaluated by Cell Titer-Glo 2.0 (Promega) according to manufacturer instruction.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation